2011
DOI: 10.1021/ja200561w
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Pore Evolution of Nanoporous Metal Particles for Energy Storage

Abstract: A well characterized and predictable aging pattern is necessary for practical energy storage applications of nanoporous particles that facilitate rapid transport of ions or redox species. Here we use STEM tomography with segmentation to show that surface diffusion and grain boundary diffusion are responsible for pore evolution at intermediate and higher temperatures, respectively. This unprecedented three dimensional understanding of pore behavior as a function of temperature suggests routes for optimizing por… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
45
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 26 publications
1
45
0
Order By: Relevance
“…Most recently, Kolluri and Demkowicz [34] reported that the ligament coarsening may arise from the volume diffusion by the collapse of neighboring ligaments onto each other. By scanning transmission electron microscopy, the surface diffusion and grain boundary diffusion (volume diffusion) are observed at intermediate and higher temperature, respectively [32]. These two modes give raise to different microstructure of NPG, which in turn change its thermal properties.…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…Most recently, Kolluri and Demkowicz [34] reported that the ligament coarsening may arise from the volume diffusion by the collapse of neighboring ligaments onto each other. By scanning transmission electron microscopy, the surface diffusion and grain boundary diffusion (volume diffusion) are observed at intermediate and higher temperature, respectively [32]. These two modes give raise to different microstructure of NPG, which in turn change its thermal properties.…”
Section: Methodsmentioning
confidence: 97%
“…X-ray nanotomography shows that the ligament does not have a minimal surface, but with a number of zero mean curvature and nanozero Gaussian curvature [14], the surface tension is expected to be unstable and the Au atoms are driven by the surface tension to achieve low surface energy, and may restructure more stable {111} planes [9]. Although the surface diffusion is possibly responsible for the pore/ ligament structure evolution annealed at temperature below 200°C [32], it is not sufficient to explain the experimental observations such as large volume reduction [10] and encased voids in ligaments [33]. Most recently, Kolluri and Demkowicz [34] reported that the ligament coarsening may arise from the volume diffusion by the collapse of neighboring ligaments onto each other.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8][9] We chose to adopt ah eat treatment for the removal of the polymer template because large mesoporous noble-metal particles usually exhibit good thermal stability. [9,17] Thermogravimetric measurements ( Figure S7) confirmed the successful removal of the triblock copolymer at 250 8 8Ci na ir.F urther increasing the calcination temperature facilitated template removal, but the mesoporous structure tended to collapse above 450 8 8C owing to the rapid growth of Pt nanoparticles ( Figure S1 a-c). By analyzing the (111) diffraction peaks of various samples after calcination at 250, 350, and 450 8 8Cw ith the Scherrer equation, the average sizes of the Pt nanoparticles were calculated to be 6.5, 6.5, and 19.7 nm, respectively,w hereas the average crystalline size before calcination was 5.6 nm ( Figure S1 e).…”
mentioning
confidence: 77%
“…[4][5][6] Because of their high electrical conductivity and wettability towards electrolytes, nanoporous materials might significantly boost the performance of energy storage devices. [7][8][9] Desirable properties of manufactured (nano)porous materials can be enhanced by controlling their pore structure and physicochemical properties of emerging pore networks. 10 For instance, introduction of active sites onto pore surfaces of mesoporous metallosilicate materials is a promising venue for designing novel adsorbents and catalysis.…”
Section: Introductionmentioning
confidence: 99%